Money Politics and Voter Behavior: Factors Behind Incumbent Defeat in Subang Regency’s 2024 Regional Election - Ujang Komarudin; Waluyo Handoko; Farzana Hussain (Unissula, 2025)
The defeat of incumbents in Indonesia’s 2024 concurrent regional elections reflects deeper issues in local electoral dynamics. In Subang Regency, the incumbent pair—Ruhimat and Aceng Kudus—lost despite holding office for five years and benefiting from institutional and political capital. This study aims to examine the factors behind this electoral defeat, using a sequential explanatory mixed-methods approach. Quantitative data were collected through closed-ended questionnaires from 400 voters across Subang sub-districts, while qualitative insights were drawn from in-depth interviews with five key informants. The findings reveal that while several variables influenced the outcome—including public dissatisfaction, weak campaign messaging, and fragmented political alliances—the most significant factor was political money. A total of 69.75% of respondents admitted that financial incentives had a decisive influence on their voting decisions. These findings underscore how clientelism and vote-buying practices continue to undermine the performance-based evaluation of candidates. The study concludes that political money remains a powerful determinant in regional elections, with significant implications for democratic accountability and electoral reform in Indonesia.